Analysis of Russia's Approach to Kyoto Protocol: Russia's Withdrawal from Second Commitment Period (2013-2020) - Nur Yasmin Ghafiel; Paramitaningrum Paramitaningrum (Department of International Relations, Universitas Andalas, 2020)
In 2004 Russia ratified Kyoto Protocol, one of the international agreements which focuses on climate change mitigation. Kyoto Protocol was established as a framework for countries to mitigate climate change globally by reducing their greenhouse gas emissions accordingly to their respective targets. Russia officially participated in the first commitment period of Kyoto Protocol in 2005 after ensuring the benefits by doing so. Entering the second commitment period, in 2011 Russia decided to withdraw. In consideration of Russia’s position as the largest fossil fuel energy exporter and as a country whose economy is in restoration, Russia’s approach to Kyoto Protocol is based on its interests and benefits which it gains from the framework. This paper analyzes the factors behind Russia’s withdrawal from the second commitment period of Kyoto Protocol through the perspective of offensive realism with qualitative methodology. The thesis finds that Russia’s reasoning of withdrawal was an act to protect its national interest, which is economic security, specifically its energy sector.